Review of Paraclius arcuatus species-group (Diptera, Dolichopodidae) with description of two new species - Soares, Matheus M.m.; Runyon, Justin B.; Capellari, Renato S.; Rocha, Rosaly Ale- (Zootaxa, 2023)
The Paraclius arcuatus species-group is reviewed and includes the following seven species: P. angusticauda Van Duzee, 1933, P. angustipennis Van Duzee, 1929, P. arcuatus (Loew, 1861), P. brooksi sp. nov., P. elongatus Van Duzee, 1930, P. pumilio Loew, 1872, and P. xibun sp. nov. Paraclius angustipennis, P. arcuatus and P. pumilio are redescribed based on photographs of types and additional specimens. Paraclius femoratus Aldrich, 1901 is synonymized with P. arcuatus, syn. nov. and Paraclius magnicornis Van Duzee, 1927 is regarded as a junior synonym of P. pumilio, syn. nov. An identification key, distribution maps and high-resolution photographs of species are provided. In addition, the systematic position of Paraclius is discussed.